1980
DOI: 10.1021/je60087a022
|View full text |Cite
|
Sign up to set email alerts
|

Study of the critical and azeotropic behavior of binary mixtures. 1. Critical states of perfluoromethylcyclohexane-isomeric hexane systems

Abstract: The PVT-x diagrams of five binary systems composed of the Isomers of hexane with perfluoromethylcyclohexane as the common component were determined In the critical region. All of these systems form positive azeotropes and exhibit a minimum temperature point In their critical locus curves.The measured critical points In these systems and their correlation and prediction using an extended corresponding states principle are reported In this paper.i The Ohio State University.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…4 No information is given as to how they were determined. Judging from a comment in another paper by the same group, 6 it is likely that the critical densities were obtained by extrapolating an average of dew-and bubble-point densities. The authors called this a rectilinear diameter.…”
Section: Test Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 No information is given as to how they were determined. Judging from a comment in another paper by the same group, 6 it is likely that the critical densities were obtained by extrapolating an average of dew-and bubble-point densities. The authors called this a rectilinear diameter.…”
Section: Test Of Methodsmentioning
confidence: 99%
“…The critical values in Table 2 are fitted to eqs 6-8 to within less than 0.2, 0.8, and 2.0%, respectively. Table 3 gives the constants for the critical-line representations (eqs [6][7][8] for this mixture.…”
Section: Application Of Methodsmentioning
confidence: 99%
“…It is found that the absolute deviations between our values and recommended values by NIST are all within the given error range. However, data by NIST in Table is an average of selected values which are measured by previous studies. These selected values are computed with a certain algorithm and exclude some unavailable values. The relative deviations between our values and the selected values are also calculated and presented in Figure , most of which are within ±0.50% and ±2.00% for T c and p c , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…An investigation of the PVT-x relations of a series of binary systems composed of the isomers of hexane with perfluoro- 1 The Ohio State University. * University of Delaware.…”
Section: Introductionmentioning
confidence: 99%